2014
DOI: 10.1097/nmd.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuicidal Self-Injury and Its Relation to Personality Traits in Medical Students

Abstract: Nonsuicidal self-injury (NSSI) has a high prevalence among the general undergraduate population, but as yet, no study has investigated the rate of NSSI among medical students despite the high levels of depression and suicidal ideation found in this population. Our study aimed to estimate the prevalence of NSSI and suicide attempts in German medical students and explore the associations between these behaviors and the five major personality traits. Seven hundred fourteen medical students (67% women; age range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 44 publications
(50 reference statements)
1
19
1
1
Order By: Relevance
“…As examples, individuals who are high in neuroticism report lower levels of self-compassion (Neff, Rude, & Kirkpatrick, 2006;Thurackal, Corveleyn, & Dezutter, 2016), and persons with depression and anxiety report that it might be difficult to manifest feelings of compassion, in part due to the negative experiences associated with their illness (Pauley & McPherson, 2010). Given that individuals who engage in NSSI have higher levels of neuroticism (Allroggen et al, 2014), it may be that self-compassion is stifled and, indeed, that individuals may feel as if their illness experiences make them unable to manifest or benefit from self-kindness. Yet, as we report in another study, of US veterans, it is precisely at these difficult times that self-compassion should be activated and of maximum usefulness, suggesting that -if "unlocked"and promoted, selfcompassion might be a powerful tool in the prevention of suicide (Rabon, Brooks, Kaniuka, Sirois, & Hirsch, submitted for publication).…”
Section: Discussionmentioning
confidence: 99%
“…As examples, individuals who are high in neuroticism report lower levels of self-compassion (Neff, Rude, & Kirkpatrick, 2006;Thurackal, Corveleyn, & Dezutter, 2016), and persons with depression and anxiety report that it might be difficult to manifest feelings of compassion, in part due to the negative experiences associated with their illness (Pauley & McPherson, 2010). Given that individuals who engage in NSSI have higher levels of neuroticism (Allroggen et al, 2014), it may be that self-compassion is stifled and, indeed, that individuals may feel as if their illness experiences make them unable to manifest or benefit from self-kindness. Yet, as we report in another study, of US veterans, it is precisely at these difficult times that self-compassion should be activated and of maximum usefulness, suggesting that -if "unlocked"and promoted, selfcompassion might be a powerful tool in the prevention of suicide (Rabon, Brooks, Kaniuka, Sirois, & Hirsch, submitted for publication).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing studies conducted in different age groups in Germany, adults show a lower lifetime prevalence than adolescents [ 16 , 18 20 ] or young adults [ 21 ]. This seems to be counterintuitive since lifetime prevalence should increase over the life span, as risks and exposure time accumulate.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these multiple studies from adolescent samples, only one study so far reported prevalence rates of NSSI from a young adult sample from Germany. In a study of 714 medical students (mean age: 23.1, age range: 18-35 years) a lifetime prevalence of 14.3 % of NSSI was found, thus showing lower rates than in all community samples of adolescents, that have been researched in Germany up to that point [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, openness to experience (nonconformity) predisposes individuals to experiment with different coping strategies, including self-injury [55]. High levels of neuroticism are also linked to NSSI [56,57]. Feelings of loneliness, isolation and alienation from peers and wider society are all major components of contemporary suicide and self-injury theories [58-60].…”
Section: Discussionmentioning
confidence: 99%